(untitled) (Altre Modernità, 2012)
Among the most provocative propositions inaugurated by Bachelard’s work one cannot miss his reflection on the question of imagination as “a major force of human nature” (The Poetics of Space), anticipating thus the premise that the productivity of imagination does not reside—as was usually thought—in its capacity for creating images derived from reality but in “the faculty of forming images which would surpass reality” (Water and Dreams). In pursuing these ideas, Bachelard—apart from enriching the hermeneutical apparatus around the elucidation of literary works—was able to take his writing at the center of the becoming of the imagination as well as into the transcendental phenomena of the poetic vision. His understanding of the experience of imagination as a becoming would make possible the internalization of the flow of the imagining as an organic entity which could not possibly be ascribed to pragmatic fields of representation nor to chronological or linear dimensions. My essay reflects on the above referred principles which are essential to Bachelard’s construction of his poetics of imagination. Additionally, I contextualize these ideas with an analyses of the imaginative processes found in Pedro Prado’s work Alsino, a poetic novel that can be situated in the antipodes of rationality since its drive for the construct of the ascensional pertain to both the realm of the oneiric, and the plane of an enduring psychical energy.